Information and Communication Technologies in Education, Research, and Industrial Applications : 13th International Conference, ICTERI 2017, Kyiv, Ukraine, May 15-18, 2017, Revised Selected Papers /: 13th International Conference, ICTERI 2017, Kyiv, Ukraine, May 15-18, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available